Dietary Supplementation of Purified Amino Acid Derived from Animal Blood on Immune Response and Growth Performance of Broiler Chicken - Wandita, T. G.; Joshi, N.; Nam, I. S.; Yang, S. H.; Park, H. S.; Hwang, S. G. (Tropical Animal Science Journal, 2018)
The existences of protein are important to supply nutritional requirements and to support optimal growth performance in modern broiler chicken. The present experiment was conducted to evaluate the effect of purified amino acid (PAA) isolated from animal blood on growth performance and immune response. A total of one hundred of 1-day old broiler chicken were used in the experiment, following a completely randomized design of 4 groups of treatment differed in concentrations of PAA supplementation (T1: control, no PAA addition; T2: 0.05%; T3: 0.1%; and T4: 0.5%) with 4 replicates for each group. Levels of various cytokines, such as IgA, IgG, interleukin (IL)-2, IL-6, tumor necrosis factor α, and interferon γ, were analyzed using an ELISA kit. Insulin-like growth factor 1, an important growth hormone, was also examined using an ELISA kit. The present result showed feed efficiency and average daily feed intake of broiler chicken increased significantly along with increasing concentrations of PAA (P